Flavonoid and phenolic compound in various parts of Hiptage candicans Hook.f. and the afford toward the lymphocyte and monocyte in BALB/cAJcl mice - พันแสง, สุรางค์รัตน์; แก้วกรม, พวงผกา (Health Science, Science and Technology Reviews, 2019)
The aim of the study is to determine the amount of flavonoid and phenolic compound, comparison between root, stem and leave of Hiptage candicans Hook.f. The highest composition of flavonoid/phenolic was 13.7 ± 0.04 และ 20.0 ± 0.7 mg per 100 mL of the crude extract. The extracts were fed orally to BALB/cAJcl mice. The percentage of lymphocyte among the control: experimental group was decreased of 71.4/33.1 and 67.3/49.0, while the monocyte was increased of 19.2/43.0 and 23.0/37.2 at 2 and 4 week, respectively. In conclusion, the extract afforded the decrease of lymphocyte as oppose to the increase of monocyte.